THE EFFECT OF QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY ON STUDENTS' READING INTEREST AND READING COMPREHENSION ABILITY - Nur Anisa Utami (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to describe reading interest and reading comprehension ability of fourth grade elementary school students through the Question Answer Relationship (QAR) strategy. This type of research is a quasi-experimental design with nonequivalent control group design. The research sample was fourth grade students at SD Inpres Bontoala I Gowa, totaling 60 students. Data collection on reading interest was carried out through a questionnaire technique and reading comprehension ability was collected through a test technique. The collected data were analyzed through descriptive and inferential analysis techniques consisting of independent sample t tests and manova tests. The results showed that there was an increase in the average reading interest and reading comprehension ability of students through the QAR strategy, so it can be concluded that the QAR strategy can increase reading interest and reading comprehension ability of fourth grade students of SD Inpres Bontoala I Gowa.